2004
DOI: 10.1073/pnas.0403743101
|View full text |Cite
|
Sign up to set email alerts
|

Changes in connectivity profiles define functionally distinct regions in human medial frontal cortex

Abstract: A fundamental issue in neuroscience is the relation between structure and function. However, gross landmarks do not correspond well to microstructural borders and cytoarchitecture cannot be visualized in a living brain used for functional studies. Here, we used diffusion-weighted and functional MRI to test structurefunction relations directly. Distinct neocortical regions were defined as volumes having similar connectivity profiles and borders identified where connectivity changed. Without using prior informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
621
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(656 citation statements)
references
References 50 publications
31
621
4
Order By: Relevance
“…These two regions have been previously differentiated in the monkey (Dum and Strick, 1991;Matelli et al, 1991;Matsuzaka et al, 1992). Since then, this demarcation has been supported in humans across studies using cytoarchitectonic data (Vorobiev et al, 1998;Geyer et al, 2000a), PET (Fink et al, 1997), functional MRI (Deiber et al, 1999), diffusion tensor imaging , and diffusion weighted imaging (Johansen-Berg et al, 2004). The boundary between pre-SMA and SMA proper estimated by the ALE method remained consistent at y = 0mm throughout the coronal plane (Fig.…”
Section: Pre-sma Vs Sma Propersupporting
confidence: 53%
See 1 more Smart Citation
“…These two regions have been previously differentiated in the monkey (Dum and Strick, 1991;Matelli et al, 1991;Matsuzaka et al, 1992). Since then, this demarcation has been supported in humans across studies using cytoarchitectonic data (Vorobiev et al, 1998;Geyer et al, 2000a), PET (Fink et al, 1997), functional MRI (Deiber et al, 1999), diffusion tensor imaging , and diffusion weighted imaging (Johansen-Berg et al, 2004). The boundary between pre-SMA and SMA proper estimated by the ALE method remained consistent at y = 0mm throughout the coronal plane (Fig.…”
Section: Pre-sma Vs Sma Propersupporting
confidence: 53%
“…However, the anatomy of the cingulate sulcus is highly variable between subjects (Vogt et al, 1995;Paus et al, 1996), and cellularly the borders between MPMC and CMA can be difficult to define (Russo et al, 2002;Johansen-Berg et al, 2004). The ventral limit of MPMC, as determined by our analysis, varied depending on its rostro-caudal location (Fig.…”
Section: Ventral Limit Of Mpmcmentioning
confidence: 85%
“…If human structural connection networks can be reliably partitioned into tens or hundreds of distinct network modules, then it is expected that these modules will correspond to functionally localized subdivisions of the brain. Indeed, connectionbased subdivisions of premotor cortex (Johansen-Berg et al, 2004) have been found to correspond closely to the subdivisions identified using functional imaging of motor and linguistic tasks in the same individuals, and connection-based subdivisions of thalamus (Zhang et al, 2008) as well as inferior frontal cortex (Anwander et al, 2007) and cingulate cortices (Beckmann et al, 2009) have been found to match the canonical functional parcellations of these areas. In a less function-specific vein, other groups have investigated the relationship, across the brain, between so-called "functional connectivity" which is assessed using correlations in resting-state BOLD signal with structural connectivity identified using diffusion imaging (Greicius et al, 2009;Hagmann et al, 2008;Honey et al, 2009;Koch et al, 2002;Skudlarski et al, 2008;van den Heuvel et al, 2008van den Heuvel et al, , 2009van den Heuvel et al, 2009;Van Dijk et al, 2010).…”
Section: Functional Connectomicsmentioning
confidence: 62%
“…Cross‐correlation was calculated between the rsFC patterns of all voxels in ROI and applied for automatic parcellation (Johansen‐Berg et al., 2004). …”
Section: Methodsmentioning
confidence: 99%